The Prevention of Juvenile Delinquency is an Essential Part of Public Safety. A Justice without a Human Face is not Justice - Villalobos Mendoza, Hector Manuel (2024)
Children and youth are the future, they are our destiny, and they are the nation's treasure. They require special attention, and their consideration is of paramount interest. This priority in decision[1]making should not be focused on only when an investigation for criminal law infringement has been initiated; on the contrary, measures aimed at preventing infringement should be opted for. The situation of vulnerability may arise when accessing justice, especially when there is a situation of weakness and incapacity to fully exercise their rights before the relevant authority. We must serve with singular determination and forge strategic alliances with state entities to carry out prevention policies and activities. Greater citizen security leads to greater tranquility, greater enjoyment, and fulfillment of rights.